2007
DOI: 10.1161/atvbaha.106.136325
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein Attenuates Inflammation and Coagulation Response on Endotoxin Challenge in Humans

Abstract: Objective-Low high-density lipoprotein (HDL) cholesterol is a strong independent cardiovascular risk factor, which has been attributed to its role in reverse cholesterol transport. Whereas HDL also has potent antiinflammatory effects, the relevance of this property remains to be established in humans. In the present study, we evaluated whether there is a relation between HDL and sensitivity toward a low-dose endotoxin challenge. Methods and Results-Thirteen healthy men with genetically determined isolated low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 27 publications
7
69
0
2
Order By: Relevance
“…Binding to HDL inhibits LPS interaction with cell surface toll-like receptor 4 (TLR-4) (Underhill and Ozinsky 2002) and LTA interaction with TLR-2 (Flo et al 2000), receptors known to mediate inflammatory responses (macrophage activation, cytokine release). These neutralising effects of HDL have been confirmed in humans with low HDL levels who show a more robust inflammatory response to LPS administration (Birjmohun et al 2007).…”
Section: Bacterial Pathogensmentioning
confidence: 87%
“…Binding to HDL inhibits LPS interaction with cell surface toll-like receptor 4 (TLR-4) (Underhill and Ozinsky 2002) and LTA interaction with TLR-2 (Flo et al 2000), receptors known to mediate inflammatory responses (macrophage activation, cytokine release). These neutralising effects of HDL have been confirmed in humans with low HDL levels who show a more robust inflammatory response to LPS administration (Birjmohun et al 2007).…”
Section: Bacterial Pathogensmentioning
confidence: 87%
“…In addition, there was an inverse association between WBC count and HDL-C. HDL cholesterol has consistently shown an inverse association with systemic markers of inflammation in many prospective studies 5,24,28 . A recent study by Birjmohun et al 29 have demonstrated that apparently healthy individuals with genetically determined isolated low HDL-C levels are more susceptible to low-dose endotoxin challenge in comparison with subjects with normal or high HDL-cholesterol levels. The study revealed a strong inverse association between HDL-C and apo A-1 levels versus leukocyte response and plasma CRP levels, supporting an antiinflammatory effect of HDL-C.…”
Section: Discussionmentioning
confidence: 99%
“…Low HDL-C levels inversely correlate with the severity of septic disease and associate with an exaggerated systemic inflammatory response (Wendel et al 2007), although it is difficult to establish whether changes in plasma lipoproteins simply reflect the severity of disease or they can directly modify the host response to inflammation. Also in healthy subjects low HDL levels are associated with increased inflammatory response on endotoxin challenge compared to subjects with normal or high HDL levels (Birjmohun et al 2007), without differences in the HDL proteome (Levels et al 2011). These observations indicate a positive role of HDL in the protection against sepsis.…”
Section: Interaction Of Hdl With Lps and Gram-negative Bacteriamentioning
confidence: 91%